Space-time localization in one-dimensional problems with free boundary for nonlinear second-order equations - Bittiev, Kh. R. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We investigate the effect of space localization and stabilization for finite time for thermal and diffusion processes that take place in active media and are described by nonlinear evolution equations.